Response of groundnut (Arachis hypogaea) cultivars to integrated nutrient management on productivity, profitability and nutrient uptake in NEH Region - BAISHYA, L K; ANSARI, M A; SINGH, ROBEN; DEKA, B C; PRAKASH, N; NGACHAN, S V (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at Nagaland during 2009 and 2010 to study the response of groundnut (Arachis hypogaea L.) cultivars to integrated nutrient management on productivity, profitability and nutrient uptake in NEH Region on a sandy loam soil. Among the cultivars, FeSEG 10 recorded significantly higher growth, yield attributes and pod yield as compared to JL 24 and FeSEG 8. Nutrients uptake (N, P and K) and nutrients use efficiency was significantly higher under ICGS 76 followed by FeSEG 10 and FeSEG 8. The highest net returns, B: C ratio and crop profitability were recorded with FeSEG 10 followed by ICGS 76. The results showed significant increase in all yield attributes, yield, nutrient uptake and economics due to the application of 75% N through inorganic fertilizers + 25% N through FYM followed by 100% N through inorganic fertilizers.